Sorption Equilibrium Studies of Toxic Nitro-Substituted Phenols on Fly Ash - B.K. Singh; Preeti Sagar Nayak (Adsorption Science & Technology)
The potential of fly ash, a low cost and abundantly available material with good sorption properties, for removing phenols was investigated. Nitro-substituted phenols, i.e. o -nitrophenol, m -nitrophenol and p -nitrophenol, were selected for the studies. The effect of various factors such as adsorbent particle size, pH, phenol concentration and temperature on the sorption capacity was investigated. The removal of nitro-substituted phenols increased with decreasing adsorbent particle size, pH and increasing concentration and temperature. Langmuir adsorption isotherm constants were calculated and it was shown that the adsorption data for phenols onto fly ash fitted the Langmuir model well. The adsorption of the nitrophenols studied followed first-order rate kinetics. Thermodynamic studies were also undertaken and the values of the standard free energy (ΔG 0 ), enthalpy (ΔH 0 ) and entropy (ΔS 0 ) changes calculated.